Just one day eaudiobook - Forman, Gayle (Just One Day, 2013)
When sheltered American good girl Allyson first encounters laid-back Dutch actor Willem at an underground performance of Twelfth Night, there's an undeniable spark. So when fate brings them together a second time, Allyson takes an uncharacteristic leap, changes course, and follows Willem to Paris. After just one day together, the spark bursts into a flame...until Allyson wakes up after a whirlwind day shocked to discover that Willem is gone. A life upended in one day turns into a year of self-discovery as Allyson embarks on a journey to break free from a lifetime of limits in order to find her true passions, and maybe even a true love.